Biological Barriers in Drug Delivery (Asian Journal of Pharmaceutics (AJP), 2024)
The concept of biological barriers to drug delivery is crucial for the development and optimization of pharmaceuticaltreatments. These obstacles represent complex and dynamic physiological systems within the human body that mustbe navigated by drugs to reach the intended target sites. Key biological barriers include blood-brain barrier (BBB),gastrointestinal (GI) barrier, placental barrier during pregnancy, and immune system. The BBB is a selective interfacecreated by endothelial cells present in the blood arteries of the brain that restricts the flow of many medications, makingit difficult to treat neurological illnesses. However, because the medicine comes into contact with different enzymesand transporters in the digestive system, the GI barrier may have an impact on drug absorption and bioavailability. Inpregnancy, the placental barrier protects the developing fetus from potential harm, but it can also limit access to the fetalcirculation of drugs. While the immune system is primarily responsible for protecting the body from foreign invaders,it can also act as a facilitator and a barrier to drug delivery. Immunotherapies use the immune system to target cancercells, but the immune response may also lead to drug clearance or side effects. Understanding and addressing thesebiological barriers is crucial for drug design, formulation, and delivery strategies. Researchers and pharmaceuticalcompanies continue to innovate to optimize drug delivery systems, enabling drugs to overcome these challenges andachieve their intended therapeutic targets effectively and safely. The development of novel drug delivery technologiesand strategies promises to provide more precise and effective treatments for a wide range of diseases.